Sobrecarga de informação no processo decisório: o papel da motivação epistêmica na resposta individual - Avelino, Ana Flávia Andrade (2015)
This study aimed to verify the influence of epistemic motivation in decision making. We addressed the following themes: decision-making, information overload; epistemic motivation; amount of information, satisfaction, and confusion. In order to achieve this purpose, we developed a task context in which it was possible to study multiple objectives in multiple scenarios, with the aid of a Multiple Criteria Decision Support System (MCDSS) and without the aid of a MDA. We carried out an experimental research in the laboratory using a decision task with multiple alternatives and criteria, with twenty-nine people divided into three experimental groups according to the number of attributes and alternatives. The task, which simulates the purchase of a bottle of wine for personal consumption, was structured in order to create a decision environment with the help of the MCDSS M-MACBETH or without it, by using the Think Aloud verbal protocol. After formulating and testing the hypotheses, we found that the effect of the information overload is not weaker for individuals with high epistemic motivation; the moderating effect of epistemic motivation was not weaker for the alternatives than for attributes; and individuals with low epistemic motivation did not notice the overload in the form of alternatives and attributes, resulting in dissatisfaction and/or confusion. Thus, we found no statistical evidence to confirm the hypotheses of this study. The discussion of the results reveals important particularities in decision-making process since participants had to choose, and people usually avoid or postpone their choices. By pointing to the role of complexity of information, a broader conception of choice is suggested. This broader perspective should allow forecasts which variables that can facilitate or hinder the emergence of effects of information overload. Regarding epistemic motivation, the findings do not reveal significant differences in the distributions of choices made according to different motivational conditions. This suggests that when faced with complex information, everyone makes the necessary effort, whether they are high or low in epistemic motivation; however, we emphasize that this topic needs further clarification.